FACTOR INFLUENCING MOBILE NUMBER PORTABILITY(MNP) IN KENYA: THE CASE OF AFRICA NAZARENE UNIVERSITY - Githii Stephen Kagwathi; John Njau Kamau; Mary Muthoni Njau; Elias Kiarie Kagiira (European Scientific Journal, ESJ, 2013)
The much awaited mobile number portability took effects in Kenya on April 1st 2011. The objective of porting was to accord consumers flexibility of shifting from one service provider to another without worrying of loosing their preferred numbers. The free movement of subscribers was expected to open a new competition front within the telephony market, with the small operators expected to benefit. However the porting process has not been so smooth. Over a year since the process started, only 47,206 subscribers have switched out of the possible twenty two million. Methodology: The study used descrptive design whereby a sample of 142 subscribers was taken. Ten factors were identified as influencing mobile number portability in kenya. These were exit barriers, cost, process,customer service, satisfaction among others.